Anaesthetic efficacy of table salt on two live fishes Anabas testudineus and Channa punctatus - Parween, Selina; Ahsan, Md Kamrul; Alam, M Manjurul (Jahangirnagar University Journal of Biological Sciences, 2016)
Different concentrations of table salt (NaCl) were evaluated for its induction/anaesthetic and physiological effects on two live fish species viz., Anabas testudineus (Koi) and Channa punctatus (Taki). The time taken to immobilize and fully anaesthesize the fishes were quite long, 36-52.83 hours and 37.75-53 hours respectively for Koi, 64.50-71.50 hours and 68.25- 71.50 hours respectively for Taki, but thereafter a quick mortality occurred in both species. The induction time was negatively related with the concentrations of salt, and independent of the intrinsic factors (total length and total weight) of the fish. No changes in the colours of skin, eye and gill were observed at lower concentrations were observed in A. testudineus, but the eye and gill were found to be affected at low concentrations in C. punctatus, irrespective of the exposure time. Table salt produced a bad smell at all concentrations at longer exposure in both species of fish. Jahangirnagar University J. Biol. Sci. 4(1): 41-49, 2015 (June)